O enfermeiro frente à Sistematização da Assistência de Enfermagem (SAE) da pessoa idosa hospitalizada - Leoncio, Cleber Silvestre (2010)
The study it aims at to investigate the nurse front to the systematization of the assistance of nursing (SAE) of the hospitalized elderly. One searched to identify to the perception of the nurses front to the systematization of the nursing assistance, and as it identifies and it recognizes the necessities of the hospitalized elderly. With regard to the methodological delineation, one was about an exploratory, descriptive study and with qualitative boarding. The research was developed in a hospital institution characterized as hospital of education, filantrópico, and generality, located in the city of São Paulo. The citizens of the study had been 43 nurses who act in the units of internment of the institution study field. The criterion of choice of the units occurred for the elderly occupation hospitalized, defining the units of choice of the study. The data had been collected by means of composed questionnaire twopiece, where the first one identifies to the citizen of the research and some questions of multiple choice fronts to the thematic one of the elderly. The second composed part for one asks opened noted, where the citizen discourses its perception in carrying through the SAE of the hospitalized elderly. The nurses consider that he has contact with the elderly in the daily development of its work, but express difficulty to carry through the systematization of the nursing assistance, for believing that the phase of the formation, that is, the graduation presents a gap of formation in regards to the assistance specifies for elderly. In the perception of the majority of the nurses the graduation was imperfection in the learning to subsidize knowledge to attend the elderly. The answers of the citizens had been analyzed through the content considered for Bardin (1977), disclosing that the searched citizens present difficulties in attending the hospitalized elderly. After analysis of the contents we group the results of the answers gotten for similarity in dimensions proposals for Dellors (1996), structuralizing abilities for superior education in the sources of knowing to be, to know to make, to know to know and to know to coexist. The pointers of this study that could be enclosed as suggestion in the superior formation. Promoting a multidimensional assistance when taking care of the hospitalized elderly